2004
DOI: 10.1186/1476-511x-3-16
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Malnutrition, anemia and increased atherosclerosis are the main causes of mortality in hemodialysis patients. Therapies designed to improve the disorders might therefore be expected to improve outcome. The effects of Nandrolone Decanoate (ND), in 64 stable hemodialysis patients, were studied with respect to the following parameters: nutritional status, hematological indexes, lipid profiles including serum levels of lipoprotein(a) [Lp(a)] in terms of differences in apolipoprotein(a) [apo(a)]. The patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Frankenfeld et al reported that administration of supraphysiological doses of ND alters glucose metabolism and lipid profile in wistar rats [21]. Experimental study indicated that ND administration in hemodialysis patients has beneficial effects but alters lipid profile by increasing the serum cholesterol and triglyceride [22]. Our findings showed that HDL value in group T was significantly increased compared to other groups and are in agreement with those of lectures and they showed that supraphysiological ND administration for eight weeks in male rats alters the lipid profile.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Frankenfeld et al reported that administration of supraphysiological doses of ND alters glucose metabolism and lipid profile in wistar rats [21]. Experimental study indicated that ND administration in hemodialysis patients has beneficial effects but alters lipid profile by increasing the serum cholesterol and triglyceride [22]. Our findings showed that HDL value in group T was significantly increased compared to other groups and are in agreement with those of lectures and they showed that supraphysiological ND administration for eight weeks in male rats alters the lipid profile.…”
Section: Discussionsupporting
confidence: 82%
“…Our findings showed that HDL value in group T was significantly increased compared to other groups and are in agreement with those of lectures and they showed that supraphysiological ND administration for eight weeks in male rats alters the lipid profile. Ghorbanihaghjo et al investigated that hemoglobin and hematocrit value in hemodialysis patients improved after ND administration [22]. Urhausen in 2003 showed that Blood parameters (hemoglobin, leucocytes and platelets) in 32 male bodybuilders and power lifters who consumed anabolic steroids were significantly higher than references [23].…”
Section: Discussionmentioning
confidence: 99%
“…Several authors, after a period of administration of AASs, highlighted a significant increase of low-density lipoprotein (LDL) and decreasing high-density lipoprotein (HDL). Such effects and reversibility are dependent on dosage and treatment duration [ 30 , 42 , 43 ]. It has been shown that high doses of AASs induce adverse effects by increasing plasma triglyceride levels and decreasing plasma HDL-C levels up to 70%, considered to provide anti-atherosclerotic protection [ 44 ], while some studies showed contradictory results about this aspect [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pro-aggregatory effects on platelets because of high dosages of androgens could be related to a decrease in cycloxygenase activity [ 68 ]. Most of these alterations could lead to an increased thrombosis risk or atherosclerotic effects on vessels [ 42 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, an observational study wherein hemodialysis patients were administered nandrolone were observed to exhibit improvements in albumin, cholesterol, and lipoprotein suggestive of nutritional benefits of androgen supplementation in ESRD patients. [28] Finally, as androgen use preceded the advent of erythropoietin, prior research has shown the utility of androgen replacement in correcting anemia of renal disease. Indeed, a recent meta-analysis comparing nandrolone vs. erythropoietin in the treatment of anemia of renal disease showed no significant difference in hemoglobin level across the two groups.…”
Section: Discussionmentioning
confidence: 99%